Types of Innovation in Islamic Religious Education Learning Methods - Mahrus (Mazidah: Journal Of Educational Research, 2026)
This study aims to identify and describe various types of innovative learning methods in Islamic Religious Education (IRE) in order to respond to contemporary challenges and the requirements of the Merdeka Curriculum. The research method used was a descriptive qualitative approach with a literature review, in which data was collected from scientific journals and relevant books, then analyzed using thematic and content analysis techniques. The results of the study show that innovation in IRE teaching methods is a necessity to shift the paradigm from passive teaching to active, student-centered learning facilitation. The conclusion of the study confirms that the integration of various methods, such as inductive, dialogue, circle (halaqah), history, and field trip methods, is very effective in improving religious literacy, critical thinking, and the internalization of Islamic values in an applicable manner. With the right combination of methods, PAI is expected to produce graduates who are intellectually competent as well as spiritually and morally strong in the midst of the complexities of the modern world.